Small-Molecules Selectively Modulate Iron-Deficiency Signaling Networks in Arabidopsis - Kailasam, Sakthivel; Chien, Wei-Fu; Yeh, Kuo-Chen (Frontiers in Plant Science, 2019)
Plant growth requires optimal levels of iron (Fe). Fe is used for energy production, numerous enzymatic processes, and is indispensable for cellular metabolism. Recent studies have established the mechanism involved in Fe uptake and transport. However, our knowledge of Fe sensing and signaling is limited. Dissecting Fe signaling may be useful for crop improvement by Fe fortification. Here, we report two small-molecules, R3 and R6 [where R denotes Repressor of IRON-REGULATED TRANSPORTER 1 (IRT1)], identified through a chemical screening, whose use blocked activation of the Fe-deficiency response in Arabidopsis thaliana. Physiological analysis of plants treated with R3 and R6 showed that these small molecules drastically attenuated the plant response to Fe starvation. Small-molecule treatment caused severe chlorosis and strongly reduced chlorophyll levels in plants. Fe content in shoots was decreased considerably by small-molecule treatments especially in Fe deficiency. Small-molecule treatments attenuated the Fe-deficiency-induced expression of the Fe uptake gene IRT1. Analysis of FER-LIKE IRON-DEFICIENCY-INDUCED TRANSCRIPTION FACTOR (FIT) and subgroup Ib basic helix-loop-helix (bHLH) gene (bHLH38/39/100/101) expression showed that R3 affects the FIT-network, whereas R6 affects both the FIT and Ib bHLH networks. An assessment of the effects of the structural analogues of R3 and R6 on the induction of Fe-dependent chlorosis revealed the functional motif of the investigated chemicals. Our findings suggest that small-molecules selectively modulate the distinct signaling routes that operate in response to Fe-deficiency. R3 and R6 likely interrupt the activity of key upstream signaling regulators whose activities are required for the activation of the Fe-starvation transcriptional cascade in Arabidopsis roots.